Physical activity and lymphoid neoplasms in the European Prospective Investigation into Cancer and nutrition (EPIC). - van Veldhoven, C; Khan, A; Teucher, B; Rohrmann, S; Raaschou-Nielsen, O; Tjønneland, A; Overvad, K; Vigl, M; Boeing, H; Benetou, V; Trichopoulou, A; Trichopoulos, D; et al. (2011)
BACKGROUND: Lymphoid neoplasms are a heterogeneous group of cancers that originate in the lymphatic cells of the immune system. Several risk factors have been identified or suggested, but they all account for only a small proportion of the lymphoid neoplasm incidence. It has been hypothesised that regular exercise may modulate the immune system and thereby reduce the risk of developing the disease. DESIGN AND METHODS: The European Investigation into Cancer and Nutrition (EPIC) cohort consists of 521,457 adults, recruited by 23 centres in 10 European countries. The analytical cohort included 343,756 participants, with 778 non-Hodgkin lymphoma (NHL) cases (376 men and 402 women) and 690 B-cell non-Hodgkin lymphoma (B-NHL) cases (326 men and 364 women). Multivariate Cox regression models were used to calculate hazard ratios (HR) for the association between total, recreational, occupational, and household physical activity and NHL and B-NHL risk, as well as the risk for several B-NHL subtypes. Models were stratified by study centre and age at recruitment and adjusted for various potential confounding factors. RESULTS: We found no evidence of any effect of total physical activity on NHL (adjusted p-trend=0.76 and 0.30 for men and women, respectively) and B-NHL risk (adjusted p-trend=0.99 and 0.21 for men and women, respectively) for either men or women. Also no robust results were found for B-NHL subtype analyses among men or women. CONCLUSIONS: This study provided no consistent evidence for an association between various physical activity measures and the risk of lymphoid neoplasms or any of the B-NHL subtypes.